The Resilience of Single Mothers with Special Needs Children in Supporting Their Education and Fulfilling Their Needs During The COVID-19 Pandemic - Wylen Djap; Angaripeni Mustikasiwi; Oki Hermawati; Dadang Irawan; Erwin Santosa (Indonesian Journal of Disability Studies, 2021)
A single mother has to face quite complicated conditions, especially for children with special needs during the Covid-19 pandemic. Many activities have changed due to large-scale social restrictions in Jakarta and its surroundings, including studying and teaching. All educational activities are conducted online. Single mothers have to consider fulfilling their children's needs while dealing with their children doing online school. This qualitative research uses a phenomenological study of four single mothers as participants with special needs children aged 15-22 years who struggle to raise them. This study shows that mothers have strong resilience because they adapt to conditions and need support from family, friends, and the environment.